Naked Surgeons? The Debate About What to Wear in the Operating Room. (29th May 2017) - Bartek, Matthew; Verdial, Francys; Dellinger, E Patchen
Abstract : Literature on operating room attire cites air sampling and environmental culture without evidence regarding surgical site infection risk. Evidence is limited to use of sterile gowns and gloves. Naked surgeons shed fewer bacteria into the operating room environment than those wearing scrub suits. Abstract: There has been recent controversy regarding recommendations and regulations concerning operating room attire. We performed a nonsystematic literature search regarding operating room attire and surgical site infection (SSI) risk. Much of the literature relies on air sampling and culture of operating room equipment but does not present evidence regarding effect on SSI risk. There is no evidence regarding SSI risk related to operating room attire except for sterile gowns and the use of gloves. Naked surgeons shed fewer bacteria into the operating room environment than ones wearing scrub suits.